SOCIAL MEDIA AS A MODERATING VARIABLE OF GOVERNMENT TOURISM STRATEGY AND THE ROLE OF LOCAL YOUTH ON REGIONAL TOURISM PROGRESS STUDY OF SIDEBUK-DEBUK HOT SPRINGS TOURIST ATTRACTION IN KARO REGENCY - Sharina Amanda; Ayu Wirda Ningsih; Mahyudin; Muhammad Fathoni; Nasib (ZILLZELL MEDIA PRIMA, 2023)
Having tourist attractions in one area will benefit the area in terms of business transaction turnover, where visitors from outside the area will come to places where tourism can attract foreign residents. The presence of foreign residents entering the area will certainly help the regional economy, especially in tourism management areas. The research analysis method used in this research is linear regression with a moderating model. There are three ways to test regression with moderating variables, namely the interaction test, absolute difference test and residual test. The population in this study is tourist visitors who come from outside the Karo district with age criteria of 20 to 50 years with a research sample of 185 people, social media is able to moderate the significant influence of the government's tourism strategy on tourism progress, the government's tourism strategy directly has a significant influence on the progress of regional tourism, social media is able to moderate the significant influence of the role of local youth on the progress of regional tourism, the role of local youth directly has a significant influence on progress regional tourism, social media directly has a significant influence on the progress of tourism in the Sidebuk-Debuk region of Karo Regency.